Counter-Reformation Sanctity in Global and Material Perspective - Noyes, Ruth S. 19XX- (Sanctity in Global Perspective Series, 2024)
This book explores the making of saints' cults in the early modern world from an interdisciplinary perspective, considering the entangled roles of materiality and globalization processes.